AN ANALYSIS OF TEACHERS’ KNOWLEDGE AND PRACTICES OF EFFECTIVE CLASSROOM MANAGEMENT: CASE STUDY IN SD CIPTA DHARMA DENPASAR - Paramita, P. A. Siska; Seken, I Ketut; Putra, I.N. Adi Jaya (Universitas Pendidikan Ganesha, 2013)
Abstract The purpose of this study was to investigate teachers? knowledge about effective classroom management and their classroom management practices for teaching English in SD Cipta Dharma Denpasar. It was also investigating the correspondence between teachers? knowledge and the practices. This study designed using qualitative case study approach. The data was obtained using multiple-choice typed test, observation checklist, and interview. The subjects were four English teachers and their students as supporting subject. The data obtained was analyzed using interactive model proposed by Miles and Huberman. The data revealed that the subjects had variety of knowledge about classroom management; one of them had sufficient knowledge , another one showed average result and the other two were emerging. In their classroom management practice, two teachers performed effective classroom management skill, but the other two showed average effort in managing their class. For the correspondence, it was found that there were three group of teachers; the first group has sufficient knowledge and applied it simultaneously, the second group has average knowledge but applied it in more effective ways, and the third group has emerging knowledge and applied it likely to be the same as their knowledge in the classroom management practice. Keywords : effective classroom management, knowledge, practice, correspondence